2008
DOI: 10.1007/s11294-008-9194-3
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Indicator of Satisfaction Chosen

Abstract: Satisfaction, Consumer, Indicator,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It can also be seen that three types of indicators have typically been used: quality (bad ... excellent, very bad ... very good); in accordance with (completely agree ... completely disagree, very satisfied ... not satisfied); and importance (not important ... very important). It is necessary to take into account that when studying the consequences of the type of indicator chosen, Raya (2009) found that although initial assessments showed no significant differences, the effects on the variables can be very important because each indicator has specific characteristics, concluding that the use of an unsuitable indicator can be misleading.…”
Section: Indicators Of Safety Perceptionmentioning
confidence: 99%
“…It can also be seen that three types of indicators have typically been used: quality (bad ... excellent, very bad ... very good); in accordance with (completely agree ... completely disagree, very satisfied ... not satisfied); and importance (not important ... very important). It is necessary to take into account that when studying the consequences of the type of indicator chosen, Raya (2009) found that although initial assessments showed no significant differences, the effects on the variables can be very important because each indicator has specific characteristics, concluding that the use of an unsuitable indicator can be misleading.…”
Section: Indicators Of Safety Perceptionmentioning
confidence: 99%